Analisis Pertanggungjawaban Pidana Terhadap Pencucian Uang Yang Menyembunyikan Aset Melalui Investasi Keluarga - Pratama, Alexander; Berutu, Sigar P.; Suseno, Jarot Jati Bagus; Tarigan, Agatha Cristie Br (Lex Stricta : Jurnal Ilmu Hukum, 2026)
This study focuses on the analysis of criminal liability in money laundering cases involving the concealment of assets through family investments. The objective is to examine the legal framework regarding the criminal offense of money laundering through family investments and to understand the evidentiary process in such cases. Using a formative legal approach, this study analyzes criminal liability for money laundering involving the concealment of assets through family investments. The results of the study indicate that family members involved in receiving or managing assets derived from criminal proceeds may be held legally liable if it is proven that they knew or should have known the source of those assets. Pursuant to Articles 5 and 6 of Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering, any person associated with assets derived from criminal acts may be subject to criminal penalties. In proving money laundering offenses in Indonesia, the principle of the burden of proof is reversed, as stipulated in Article 77 of the Anti-Money Laundering Law.